THE ABILITY OF CURCUMIN AND 4-ARYL CURCUMIN DERIVATIVES AS RADICAL SCAVENGER OF SUPEROKSID - ., Satibi; AM, Supardjan (Indonesian Journal of Pharmacy, 2001)
Superoxide radical scavenger property of curcumin and its derivatives was investigated using Nitro Blue Tetrazolium (NBT) method. Curcumin was modified at the active methyleen groups with aryl group (4-aryl curcumin), which supposed to be related to its anti-inflamatory activity. The experiment were carried out by mixing curcumin solution at five different concentrations and superoxide radical. After incubating for 60 minutes, NBT2+ (15,29 M) was added and measured at max of 687 nm, so as the curcumin derivatives. The result showed that superoxide radical made bathochromic shift of curcumin. Bathochromic shift was higher when aryl group was attached at active methyleen C-4 of curcumin. This shift made the max of curcumin and its derivatives moving close to max of diformasan (result of NBT2+ reduction by superoxide radical), producing an overlapping spectra. The increasing concentration of curcumin and its derivatives made the increasing max of diformasan absorbance. Thus, the method of NBT2+ reduction, in fact, unable to estimate the scavenger property of curcumin and its derivatives.Key words: curcumin derivatives, superoxide radical